Variation in Fumonisin and Ochratoxin Production Associated with Differences in Biosynthetic Gene Content in Aspergillus niger and A. welwitschiae Isolates from Multiple Crop and Geographic Origins - Susca, Antonia; Proctor, Robert H.; Morelli, Massimiliano; Haidukowski, Miriam; Gallo, Antonia; Logrieco, Antonio F.; Moretti, Antonio (Frontiers in Microbiology, 2016)
The fungi Aspergillus niger and A. welwitschiae are morphologically indistinguishable species used for industrial fermentation and for food and beverage production. The fungi also occur widely on food crops. Concerns about their safety have arisen with the discovery that some isolates of both species produce fumonisin (FB) and ochratoxin A (OTA) mycotoxins. Here, we examined FB and OTA production as well as the presence of genes responsible for synthesis of the mycotoxins in a collection of 92 A. niger/A. welwitschiae isolates from multiple crop and geographic origins. The results indicate that i) isolates of both species differed in ability to produce the mycotoxins; ii) FB-nonproducing isolates of A. niger had an intact fumonisin biosynthetic gene (fum) cluster; iii) FB-nonproducing isolates of A. welwitschiae exhibited multiple patterns of fum gene deletion; and iv) OTA-nonproducing isolates of both species lacked the ochratoxin A biosynthetic gene (ota) cluster. Analysis of genome sequence data revealed a single pattern of ota gene deletion in the two species. Phylogenetic analysis suggest that the simplest explanation for this is that ota cluster deletion occurred in a common ancestor of A. niger and A. welwitschiae, and subsequently both the intact and deleted cluster were retained as alternate alleles during divergence of the ancestor into descendent species. Finally, comparison of results from this and previous studies indicate that a majority of A. niger isolates and a minority of A. welwitschiae isolates can produce FBs, whereas a minority of isolates of both species produce OTA. The comparison also suggested that the relative abundance of each species and frequency of FB/OTA-producing isolates can vary with crop and/or geographic origin.